2015
DOI: 10.1007/s10648-015-9330-6
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the Rainbow: Retrieval Practice Leads to Better Spelling than does Rainbow Writing

Abstract: In three experiments, we compared the effectiveness of rainbow writing and retrieval practice, two common methods of spelling instruction. In experiment 1 (n=14), second graders completed 2 days of spelling practice, followed by spelling tests 1 day and 5 weeks later. A repeated measures analysis of variance demonstrated that spelling accuracy for words trained with retrieval practice was higher than for words trained with rainbow writing on both tests (η p 2 =.49). In experiments 2 (second graders, n=16) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 47 publications
3
27
1
Order By: Relevance
“…• Sample sizes after attrition ranged from fewer than 20 students to nearly 400 students (Jones et al, 2016 andBjork et al, 2014, respectively) • Delays between retrieval practice and the final test ranged from one day to the end of the semester (e.g., McDaniel et al, 2013 andTu et al, 2017, respectively) As displayed in Figure 2, the majority of effect sizes (57%) indicated medium or large benefits from retrieval practice. In other words, 28 out of 49 Cohen's ds were greater than 0.50.…”
Section: )mentioning
confidence: 99%
“…• Sample sizes after attrition ranged from fewer than 20 students to nearly 400 students (Jones et al, 2016 andBjork et al, 2014, respectively) • Delays between retrieval practice and the final test ranged from one day to the end of the semester (e.g., McDaniel et al, 2013 andTu et al, 2017, respectively) As displayed in Figure 2, the majority of effect sizes (57%) indicated medium or large benefits from retrieval practice. In other words, 28 out of 49 Cohen's ds were greater than 0.50.…”
Section: )mentioning
confidence: 99%
“…In this laboratory study, primary-school students showed a retrieval practice advantage, as compared to restudy, for recall (but not recognition) both when the words were embedded in the context of a story and when they were presented alone (Goossens et al, 2014). Additionally, and relevant to word learning, retrieval practice benefits for spelling have been found in beginning spellers (Jones et al, 2016), although for adult spellers the results have been mixed (Pan et al, 2015). We are not aware of any studies examining the testing effect in L1 grammar.…”
Section: Spaced Repetition and Retrieval Practice In Language Learnmentioning
confidence: 99%
“…That assertion has since been supported by various research findings over several decades. In fact, it is now well-established among cognitive and educational psychologists that low-stakes practice testing, or retrieval practice, can serve as a more potent "memory modifier" than non-retrieval studying (Bjork, 1975), yielding pedagogical benefits in classroom settings (e.g., Agarwal et al, 2014;Pan, Cooke, et al, 2019) and across a wide range of materials (i.e., the testing effect; for reviews, see Pan & Rickard, 2018;Roediger & Karpicke, 2006b;Rowland, 2014), including spelling (e.g., Beseler, 1953;Christine & Hollingsworth, 1966;Cook, 1957;Cohen, 1969;Jones et al, 2016;Louis, 1950;Pan et al, 2015;Schoephoerster, 1962). Thus, in recommending practice testing, the Speller incorporated a second learning technique that is now widely regarded as highly potent (Dunlosky et al, 2013;Pashler et al, 2007).…”
Section: Revisiting the Horn-ashbaugh Spellermentioning
confidence: 99%
“…Two recent studies provide further insights into the value of practice testing. Across three experiments conducted in US classrooms, Jones et al (2016) had 1st and 2nd grade students first take a pretest and then learn spelling words using self-corrected tests or a method known as rainbow writing. Often appearing on lists of "fun" spelling activities, rainbow writing entails copying words multiple times in different colors.…”
Section: Reconsidering the Role Of Spelling Testsmentioning
confidence: 99%